PWE-030 The need for repeated course of intra-venous iron in IBD patients; a 7 year retrospective review. (8th June 2018) - Johnson, Matt W; Johnson, Luke; Lourenco, Floyd
Abstract : Introduction: The current prevalence of IBD in UK is said to be 400/100, 000 (0.4%), with rates for Crohn's disease ranging between 26 to 199 per 1 00 000 (<0.2%), whilst Ulcerative Colitis (UC) is found more frequently at 37 to 246 per 1 00 000 (0.25%). Anaemia is a common problem in IBD, contributing to tiredness and lethargy, and has multifactorial causes. Current ECCO guidelines recommend that all patients with IBD should be assessed for IDA and that intravenous iron should be considered first line in patients with active inflammation. We were keen to assess the need for recurrent courses of IV iron in IBD patients. Method: The Luton and Dunstable University Hospital serves a catchment of 3 30 000 and has a database of 3014 IBD patients (0.9%). This is made up of 186 Proctitis, 1447 UC, 1037 Crohn's, 71 Microscopic colitis, 273 Indeterminate colitis patients. We compiled a 7 year retrospective database of all the IBD patients presenting to the L and D with blood tests confirming iron deficiency anaemia (IDA), using the following definition; haemoglobin level of <13 g/L for men and <12 g/L for women with ferritin of <50 ng/ml (although ECCO suggest <100 ng/ml in acutely inflamed patients). We compared this with a database of all the iron infusions that had been prescribed for IBD patients over that same 7 year period. In this way the demand for recurrent iron infusions was assessed. Results: The prevalence of IBD is high in the local area (almost 1%). Over the 7 year review period, 633 (21%) of our local IBD patients were found to have IDA, with a median Hb level of 118 (130–47) g/L and ferritin count of 16.9 (49.8–2.4) ng/ml. Of these, there were 238 infusions in 128 patients (4.2% of total cohort), with 37 patients (29%) requiring 110 repeated infusions (with a range of an additional 1–17, median 2, mean 3.97). The data set was skewed by 7 patients who between them required 71 additional infusions, due to a range of co-morbidities including 1x acute GU bleed, 1x stricture surgery, 1x haemorrhoidectomy and 4x joint care with haematology. If these 7 patients were removed from the data set, just 39 repeated infusions would have been necessary in 30 patients (23%) over the 7 year period. Conclusion: The BSG have previously highlighted that 50% of IBD patients suffering IDA will redevelop it within 1 year post-correction. Our data suggests that if the patients' IDA is predominately due to their IBD (and not other co-morbidities), then IV iron is a highly effective therapy, with only 23% requiring further infusions over a 7 year period.